Hubungan Antara Konsumsi Probiotik terhadap Regulasi Emosi - Maharani, Atifah Fadilah; Berawi, Khairun Nisa; Graharti, Risti (Medula, 2024)
Digestion organs and brain communicate through specific pathway that involves nervous, endocrine, and immune system onto it. Guts microbiota especially probiotics holds a crucial matter in communicating with brain, that’s why it can affect one’s mood and cognitive functions by producing neurotransmitters that are related to brain through endocrine and autonomy nervous system. The consumption of probiotics is known to be able to improve the quality of guts microbial environment, where this matter has a profound impact in increasing mood so that a person can regulate their emotion better. A good emotion regulation has a beneficial impact in order to prevent and solve stress, anxiety, and depression. Psychosocial changes can be a stressor for individual so that the ability to regulate mood and emotion is needed to help a person adapt well. The aims of this study is to know how beneficial probiotics can be in individual mood changes. The relation between probiotics consuming and mood changes have been such an interest topics to be researched in order to gain knowledge and truth how it may give an enormous impact on people’s health by consuming it regularly. It is also proved by many articles and prior literatures that show the benefits of it in physical and mental aspects yet individual quality of life, vice versa it has negative impacts if it happens in a long-term period. Daily stressors are inevitable so that by knowing what could help to at least manage it. Managing how to face stressor isn’t easy for several people, thus it also can be fatal if it isn’t treated well, such as depression or even suicide.